Ideología, imaginarios y violencia política en los Andes durante el siglo XIX - Aljovín de Losada, Cristóbal; Velásquez Silva, David (Jahrbuch für Geschichte Lateinamerikas, 2021)
The six articles of this section study the relation between political violence, ideological aspects, and ideas of the political in the Andean countries (the current republics of Bolivia, Peru, Ecuador, and Colombia).